A 22.3% Efficient p‐Type Back Junction Solar Cell with an Al‐Printed Front‐Side Grid and a Passivating n+‐Type Polysilicon on Oxide Contact at the Rear Side. Issue 12 (29th September 2020) - Min, Byungsul; Wehmeier, Nadine; Brendemuehl, Till; Merkle, Agnes; Haase, Felix; Larionova, Yevgeniya; David, Lasse; Schulte-Huxel, Henning; Peibst, Robby; Brendel, Rolf
Abstract : The fabrication of a silicon solar cell on 6 in. pseudo‐square p‐type Czochralski grown silicon wafers featuring poly‐Si‐based passivating contacts for electrons at the cell rear side and screen‐printed aluminum fingers at the front side is demonstrated. The undiffused front surface is passivated with an Al2 O3 /SiN x stack, and the rear surface is covered with a thin oxide/n + ‐poly‐Si/Al2 O3 /SiN x layer system, contacted by screen‐printed silver fingers. A loss analysis shows that the recombination losses at the metal contacts on both cell sides dominate the total energy losses. A voltage of 700 mV as the highest open‐circuit voltage from a batch of seven cells is achieved, and the best cell efficiency is 22.3%, independently confirmed. Abstract : The polysilicon on oxide back junction approach for integrating passivating contacts in p‐type silicon solar cells is presented with 22.3% efficiency on full area of M2‐size wafers, fabricated with industrial equipment. This concept is especially attractive for current cell manufacturers since only few pieces of equipment need to be added to current passivated emitter and rear cell (PERC) production lines.